2021
DOI: 10.1108/ecam-02-2021-0165
|View full text |Cite
|
Sign up to set email alerts
|

A multivariate regression approach toward prioritizing BIM adoption barriers in the Ethiopian construction industry

Abstract: PurposeBuilding information modeling (BIM) is a process of creating an intelligent virtual model integrating project data from design to construction and operation. BIM models enhance the process of communicating the progress of construction to stakeholders and facilitate integrated project delivery, coordination and clash detection. However, barriers within the construction industry in Ethiopia has led to slow BIM adoption in the country. The aim of this paper is to identify perceived BIM barriers, provide a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 70 publications
3
17
0
Order By: Relevance
“…Moreover, all the participating AEC companies listed "the cost of training", "the cost of software", and "huge BIM upfront investment" as among the top five barriers in implementing BIM. This is consistent with other similar studies that have identified these barriers as either significant or normal barriers to BIM implementation [28,32,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. In Jordan, these results are likely because many Jordanian companies work on governmentfunded projects, while others work on private projects funded by the owner, who is also making decisions regarding the project.…”
Section: Discussion and Comparison Of The Results With Other Studiessupporting
confidence: 86%
See 2 more Smart Citations
“…Moreover, all the participating AEC companies listed "the cost of training", "the cost of software", and "huge BIM upfront investment" as among the top five barriers in implementing BIM. This is consistent with other similar studies that have identified these barriers as either significant or normal barriers to BIM implementation [28,32,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51]. In Jordan, these results are likely because many Jordanian companies work on governmentfunded projects, while others work on private projects funded by the owner, who is also making decisions regarding the project.…”
Section: Discussion and Comparison Of The Results With Other Studiessupporting
confidence: 86%
“…Despite this, in Jordan there is a reported "lack of adequate BIM guidelines". Both participating architecture and structure engineering companies ranked this barrier as the second-and third-highest barriers, while other companies ranked it as the sixth-and seventh-highest; this barrier was also noted in several other studies [37,[39][40][41][42]48]. Another significant barrier impeding BIM implementation in Jordan is "insufficient BIM technical knowledge and awareness", which was ranked first by the architecture companies, fifth by the structure engineering and quantity surveying companies, and tenth by the facility management companies.…”
Section: Discussion and Comparison Of The Results With Other Studiessupporting
confidence: 63%
See 1 more Smart Citation
“…There is a positive correlation between simplicity and usage. Owing to low availability of BIM tools, a perception of BIM complexity is created thereby hindering usage (Alemayehu et al , 2021). The steep learning curve associated BIM’s perceived complexity creates a high level of resistance to change at management levels thereby hindering BIM from thriving even in situations where lower ranked workers like graduate professionals would be willing to explore them.…”
Section: Factors Influencing Usage Of Building Information Modelling ...mentioning
confidence: 99%
“…Babatunde et al (2020a) found out that improvement of BIM usage in Nigeria from 2012 to 2015 was minimal while Ikuabe et al (2020) found out that though BIM usage was moderate in South Africa, it performed poorly compared with other technologies like Internet of Things, augmented reality and 3D printing when comparing various digital technologies being used in South Africa. BIM usage in Ethiopia is also low, with Alemayehu et al (2021) highlighting the main barriers being low competency levels, low collaboration levels and no government mandates in BIM.…”
Section: Introductionmentioning
confidence: 99%